Impact of LAB Consortia Supplementation and Teat Dipping on Haematological Parameters, Antioxidant Activity, and Total Immunoglobulin in subclinical mastitis Sahiwal Cows - Kumar, Sachin; Chauhan, Nutan; Balaga, Sravani; Singh, Ojal; Kundgir, Sumit; Samanta, Ashis Kumar (Indian Journal of Dairy Science, 2026)
The present study investigates the effects of a probiotic consortium on haematological parameters, antioxidant levels, and serum immunoglobulin concentrations in Sahiwal cows diagnosed with subclinical mastitis. A total of 24 mid-lactating cows were randomized into four treatment groups: a healthy control group (H) receiving fermented soybean meal (UFSB45), a subclinical mastitis group (M) also receiving UFSB45, a probiotic group (PRO) receiving an inoculated fermented soybean meal (IFSB45), and a combined treatment group (PRO+T) receiving IFSB45 along with topical teat dip application. The teat dip was administered at a concentration of 8.94 to 8.77 log10 CFU/ml, while the oral probiotic was given at a rate of 50 g per animal per day for 60 days. Results indicated no significant differences in dry matter intake (DMI) and body weight across treatment groups. However, hemoglobin (Hb) levels showed significant variation, with the healthy group exhibiting the highest Hb concentrations. Total leukocyte count (TLC) was significantly (p<0.05) elevated in the M group (M) compared to other groups, while lymphocyte counts were highest in the healthy group and lowest in the M group. The SOD and catalase activity (nmol/min/ml) enzyme activity were significantly highest (P<0.05) in the H group followed by PRO+T, PRO and lowest in the M group. The blood serum immunoglobulins in the PRO and PRO+T groups were significantly lower than those in the M group (P<0.01). This study concludes that administering probiotics can positively influence certain haematological and biochemical parameters in cows with subclinical mastitis, suggesting potential benefits for improving overall health in dairy cattle.